PENGARUH OBESITAS DALAM KEHAMILAN TERHADAP BERAT BADAN JANIN - Zulfadli; Jovanka Ris Natalia Sinaga; Rodiani (CV. Jasa Sukses Abadi, 2020)
Obesity is a state of imbalance in body weight and height due to excessive fat tissue in the body. The incidence rate of overweight or obesity is increasing over time and has even become a global pandemic with a prevalence of 2.1 billion in 2013, increasing from 857 million cases in 1980. Obesity can be assessed from the body mass index (BMI) where World Health Organization (WHO) classifies obesity with BMI ≥ 30 kg / m2. Obesity generally occurs in pregnancy, especially pregnancies that occur above 35 years. Obesity is a high obstetric risk because it can increase the risk of maternal and fetal morbidity and mortality. Complications that can occur in pregnant women with obesity in pregnant women are an increased risk of hypertension, gestational diabetes, spontaneous abortion and postpartum hemorrhage. The fetus can increase the risk of stillbirth in the antepartum period, intrapartum complications such as shoulder dystocia, macrosomia and increase the risk of fetal defects such as neural tube defects, spina bifida, congenital heart disease and omphalocele. Macrosomia is a condition in which the baby is born with a larger size or weight> 4000 grams, this is one of the complications of labor which causes increased morbidity and mortality in pregnancy because its complications in childbirth.